Mediating effect of identification of avatar: social phobia, depression and IGD’s symptoms - Pang, Iris Chee Yin; Lam, Ke Wei; Nah, Zi Ying (2019)
Internet Gaming Disorder (IGD) has become a concerning phenomenon in recent years but it is not taken seriously in Malaysia. The present study aims to investigate the mediating effect of identification of avatar (IOA) on the relationships between social phobia, depression, and IGD’s symptoms. A total of 702 respondents were included in the final analyses. Respondents were sampled using a purposive sampling techniq1ue with cross sectional design. A self-administrated online questionnaire which consisting of 39 items adapted from Internet Gaming Disorder Scale-Short Form (IGDS-SF), Social Phobia Scale-Short Form (SPS-SF), Montgomery-Asberg Depression Rating Scale, and The Player-Avatar Identification Scale (PAI) were used to collect data. Cognitive-behavioral model of pathological Internet use (PIU) and social identity theory were used to justify the integration of social phobia, depression and IOA and IGD’s symptoms. Multiple linear regression result indicated that social phobia, depression, and IOA were positively predicted IGD’s symptoms. IOA was the strongest predictor of IGD’s symptoms among Malaysian youth, followed by depression and social phobia. Besides, mediation analysis revealed that IOA mediates the relationship between social phobia, depression, and IGD’s symptoms. The present study sheds light on understanding the importance of the state of psychological well-being among youths. As a result, the findings of this study have important implications for individuals, parents, universities, and policy makers. In short, social phobia, depression and IOA were identified as predictors of IGD’s symptoms among youth in Malaysia.